Kebebasan Berdakwah di Youtube: Suatu Analisis Pola Partisipasi Media - Ari Wibowo (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2018)
This article describes the reality of freedom of preaching on social media. The research approach used in this study is qualitative descriptive with a critical paradigm. There are two focus of the study approach used, namely; 1) participatory culture approach, to know the characteristics of the Youtube da'wah channel, 2) a new media impact analysis approach, to analyze the problem of da'i and mad'u millennial in the context of da'wah activities on the Youtube channel. The results of this study indicate that da'wah activities on the da'wah Youtube channel consist of 4 (four) types, namely: 1) Youtube channels affiliated with community organizations; 2) Youtube channels that are managed independently by da'i; 3) youtube channel managed by da'wah community; 4) Youtube channels managed by Vloggers or other Youtuber. Also, there are threats behind the freedom to preach on social media, including; easy spread of provocative preaching messages, slander, hoax, and veiled radical understanding. The solution to the threat is; 1) the corrective approach of the da'i through Youtube channels; 2) the participation of da'i affiliates to oversee da'wah content that is inappropriate and contrary to humanist, moderate and transformative da'wah.